Enzymatic Treatment of Soft Jackfruit (Artocarpus heterophyllus) Pulp With Two Commercial Pectinases: Physical Properties and Viscosity Analysis - Lacerda Queiroz , Edinara; Bastos de Almeida, Tamires; Maria Almeida de Souza, Sílvia; Acosta Martinez, Ernesto (Journal of Applied Biotechnology, 2021)
The aim of this study was to investigate the effect of enzyme hydrolysis of jackfruit pulp using two commercial pectinase enzyme solutions with different polygalacturonase activities. A 2³ factorial design, with three repetitions at the central point, was used to establish the optimal conditions of jackfruit pulp hydrolysis, evaluating the effect of time (20 - 100 min), temperature (30 - 60ºC) and enzyme concentration (0.01 - 0.09%). The dependent variables viscosity, yield, soluble solids content, color intensity, shade, and turbidity were the responses evaluated. Viscosity, color intensity, shade, and turbidity of the pulps were significantly influenced by all studied variables with the determination coefficients (R2) between 0.74 and 0.99. The lack of adjustment was not significant in the models that describe the previous properties. The highest enzyme concentration (0.09%) was the factor with the greatest influence on the studied responses, regardless of the pectinase type.